Paresthesia and Dysesthesia after Root Canal Therapy of a Mandibular Molar: Diagnosis and Management in a Clinical Case Report - Fazlyab, Mahta; Hassani , Ali; Kamali, Siavash (Iranian Endodontic Journal, 2025)
Inferior alveolar nerve (IAN) injury is a rare but serious complication of root canal treatment (RCT), typically caused by mechanical over-instrumentation, chemical irritation from extruded sealers, or thermal damage. We report the case of a 42-year-old woman who developed persistent burning pain, numbness, and dysesthesia of the right lower lip and gingiva after RCT of the right mandibular second molar. Initial management by a general dentist involved retreatment and calcium hydroxide medicament; however, early CBCT was misinterpreted, and referral was delayed. High-quality CBCT and clinical testing later revealed obturation material within the IAN canal and a horizontal fracture of the distal root. Endodontic retreatment, followed by maxillofacial microsurgery for removal of extruded gutta-percha/sealer, combined with neuroprotective therapy (dexamethasone, vitamin B, and adjunctive low-level laser therapy). The patient achieved complete resolution of pain and sensory disturbances within one month, and remained asymptomatic with radiographic periapical healing at 12-month follow-up. Comprehensive preoperative imaging, cautious canal instrumentation, independent CBCT interpretation by the endodontist, and timely specialist referral are essential to minimize the risk of IAN injury. Even with delayed intervention, targeted microsurgical removal of extruded material can result in favorable neurological recovery.